Perkembangan gagasan pendidikan: Dari akhlak klasik hingga inovasi kontemporer Triyo Supriyatno - Devi, Anjar Aulia (Maliki Interdisciplinary Journal, 2026)
This article discusses the development of ideas in Islamic education from the classical period to the present day. The writing aims to describe changes in the orientation and approaches of Islamic education throughout history and to examine examples of their application in contemporary thought. The method used is a literature study with a descriptive approach to works from three main periods and three works by Prof. Triyo Supriyatno. The study shows that ideas in Islamic education evolved while maintaining core values such as the emphasis on morality. In the classical era, the main focus was character building and religious sciences. The modern era introduced integration with general sciences. Meanwhile, in the contemporary era, ideas such as those proposed by Triyo Supriyatno offer innovative operational methods in leadership, learning, and educational institution management. This article concludes that Islamic education continues to evolve while preserving its identity and recommends the importance of innovation relevant to the times.